(untitled) (Bangladesh Medical Journal, 2024)
Acute pancreatitis (AP) is a prompt inflammatory process of the pancreas and it may be ranged from mild to severe pancreatitis with variable involvement of regional tissues and remote organ systems. Though there are many scoring systems for adults but scarce of scoring system for assessing the severity of acute pancreatitis among paediatric cases increase their suffering. Systemic Inflammatory Response Syndrome (SIRS) can be useful for assessing the severity of acute pancreatitis in children. It is reported that SIRS has good sensitivity, specificity, positive predictive value and negative predictive value. The aim of this study was to assess the severity of acute pancreatitis in paediatric cases from the scores of SIRS. This cross-sectional descriptive study was coducted in the Department of Paediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh for a period of 1.5 years from May 2019 to October 2020. A total of 25 children with acute pancreatitis were selected purposively and SIRS was evaluated. The sensitivity, specificity, positive predictive value and negative predictive value of SIRS was calculated. Out of 25 acute pancreatitis children, 18 (mean age, 10.27±4.0 years) were diagnosed as mild AP and 7 (mean age, 10.54 ±4.0 years) as severe AP. Fourteen (56.0%) children were male and less than half 11 (44%) of children had pallor and most of them 23 (92%) had abdominal tenderness. There was no statistically significant difference between mild and severe AP in terms of serum lipase, amylase, BUN and CRP (p > 0.05). SIRS score was ≥2 in 7 (100%) severe AP patients and score was ≥2 in 4 (22.2%) mild AP patients and it was statistically significant (p=0.001). Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of SIRS score in predicting severe acute pancreatitis was 100%, 77.8%, 63.6%, 100% and 84% respectively. This study finds that SIRS score can effectively assess the severity of acute pancreatitis in the paediatric age group. Systemic Inflammatory Response Syndrome (SIRS) score at admission can be used to assess the severity of acute pancreatitis. Bangladesh Med J. 2022 Sept; 51(3): 10-17